Still Searching for Solutions: a Critical Approach to Academic Underachievement among Migrant Origin Students in Italy - Giovanna Malusà (University of Bologna, 2018)
This article analyses the most significant legislation so far enacted to protect the right-duty to education and then goes on to present some measures to support the academic success of migrant origin students, highlighting the most critical areas and the urgent need to create a vision of education with a clear political dimension and an effective ius scholae.